Sequential Conveyor Simulator berbasis PLC Omron CP1MA-30CDR-A-V1. - Mhd Rizki Syahputra; Adi Sastra Pengalaman Tarigan (CV. Hawari, 2026)
With the growing controlled system used in small industries and big industries which was originally used hard wired into Programable Logic Controller requires the students know and understand about PLC because, PLC makes it easy for user to change a system without changing the electrical circuit. The author believes that the focus of learning the philosophy of making a control system does not have to depend on a particular PLC brand. Therefore in this final project the authors designed a Sequential Conveyor Simulator. Control system is intended to control the on/off conveyor and find out how much power needed to drive the conveyor. In the control system, there are three digital inputs are sourced from the push button, sensor, and limit switch while output in the form of on/off conveyor motors. The series consists hardware and software that connect the two using a simple wiring. From the test result show the hardware and software in accordance with the design controll proces, the average power needed to move the conveyor is 13,077 watt.